The blossom and the nettle - Noble, Diane (Colorado Springs, Colorado : WaterBrook Press, 2000)
"In her sweeping new trilogy, the California Chronicles, award-winning author Diane Noble combines love and laughter, poignancy and passion in a setting that brings to life the young and gloriously wild California of yesterday."--Cover
Keywords: Inheritance and succession -- Fiction; Historical fiction